2012
DOI: 10.5009/gnl.2012.6.4.516
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Enteropathy-Type T-Cell Lymphoma Diagnosed by Small Bowel Enteroscopy: A Perspective on Imaging-Enhanced Endoscopy

Abstract: Enteropathy-type T-cell lymphoma (ETL) or enteropathy-associated T-cell lymphoma is a very rare malignant intestinal tumor. ETL is usually diagnosed by surgery. Endoscopic findings of ETL are not well known, and there are few reports of findings from endoscopy that has been performed only using white light. Additionally, there are no definite treatment guidelines for ETL. Therefore, we report a case of ETL diagnosed by enteroscopy with imaging-enhanced endoscopy and also review recently developed treatment opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…They reported that diffuse mucosal thickening and edema with multiple shallow ulcerations, and a nodular or mosaic mucosal pattern were characteristics of the disease. 8 10 In our cases, small bowel was almost always involved and colonic involvement was found in half the patients. Endoscopy of the small intestine revealed multiple circular or semicircular shallow ulcerations covered with whitish mucus-like exudate.…”
Section: Discussionmentioning
confidence: 51%
“…They reported that diffuse mucosal thickening and edema with multiple shallow ulcerations, and a nodular or mosaic mucosal pattern were characteristics of the disease. 8 10 In our cases, small bowel was almost always involved and colonic involvement was found in half the patients. Endoscopy of the small intestine revealed multiple circular or semicircular shallow ulcerations covered with whitish mucus-like exudate.…”
Section: Discussionmentioning
confidence: 51%
“…Diffuse mucosal thickening and edema with multiple shallow ulcerations, and a nodular or mosaic mucosal pattern are typically present. 34 Radiographic features in barium studies are not specific and include polypoid form, multiple nodules, infiltrative form, endoexoenteric form with excavation and fistulization, and mesenteric invasive form with an extraluminal mass.…”
Section: Resultsmentioning
confidence: 99%
“…MEITL of the small intestine is difficulty to diagnosis and is frequently associated with non-specific symptoms. Many cases are diagnosed after emergent surgery for perforation or obstruction, as occurred in this patient 6. Given the low incidence of the disease, available evidence is minimal and therefore no current guidelines exist regarding optimal diagnosis or treatment 1.…”
Section: Discussionmentioning
confidence: 99%